2010
DOI: 10.1186/1744-859x-9-36
|View full text |Cite
|
Sign up to set email alerts
|

Lower paraoxonase 1 activity in Tunisian bipolar I patients

Abstract: BackgroundThe purpose of this study was to investigate the variations of paraoxonase activity and lipid profile in bipolar I patients, and the association of this activity with the sociodemographic, clinical and therapeutic characteristics of this population.Patients and methodsOur study included 66 patients with bipolar I disorder and 64 controls aged 37.9 ± 12.6 and 36.3 ± 18.2 years, respectively. Paraoxonase activity was determined by kinetic methods; high-density lipoprotein cholesterol (c-HDL), low-densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 15 publications
(15 reference statements)
1
18
1
Order By: Relevance
“…This confirms the higher risk of cardiovascular diseases in men compared with women. In fact, previous studies suggested that mania, either directly (through factors intrinsic to illness) or indirectly (through other mediators or associated variables), increased the risk of cardiovascular disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…This confirms the higher risk of cardiovascular diseases in men compared with women. In fact, previous studies suggested that mania, either directly (through factors intrinsic to illness) or indirectly (through other mediators or associated variables), increased the risk of cardiovascular disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with a genome-wide association study reporting no associations between bipolar disorder and the Q192R polymorphism or any other polymorphism in the PON1 gene 26 . In terms of PON1 activity in bipolar patients; one study demonstrated normal activity 13 but the other showed decreased PON1 activity 20 . The results of the present study and the discrepancies between the other studies might be associated with the distinct genotypic distribution of PON1 across different ethnic populations.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies investigated PON1 activity in bipolar patients. The first one presented normal PON1 activity but the other showed decreased PON1 activity in bipolar patients 13,20 . In a study consisting of both depressed and bipolar patients; lowered PON1 activity was found to be associated with comorbid mood disorders and tobacco use disorder 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The list of tested compounds continues to grow longer. Researchers interested in the effects of antidepressants on PON1 activity have only performed in vivo studies and they emphasized the potential antioxidant activity of selective serotonin re-reuptake inhibitors, such as lithium, in bipolar disorder [18].…”
Section: Discussionmentioning
confidence: 99%